(3Mbhb GdeLfi YdjI ai GdbGfhf GdeUQi hGdbGfhf GdebGQf (B/ s - (3YdGA ahRi Rcis; (3ahRjI YHOGdSJGQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3HYO YQV GdJTQjYGJ GdebGQf GdJ JfGhdJ Mbhb GdeLfi YdjI HYjf GdGYJHGQ hcPdc GdJYOjdGJ GdJTQjYjI GdMOjKI GdJi GJNPJ HGMdGd GdhSGFd GdbGfhfjI GdMOjKI OGNd bGfhfi GdYbhHGJ hGdGLQGAGJ GdLfGFjI dEUdGM VQQ GdLQjeI GJVM Gf gPI GdVeGfGJ ZjQ cGajI hbGUQI Yf JMbjb GdgOa GdefThO hgh JhajQ GdMeGjI GdaYGdI ddeLfi YdjI hJbOe Mdhd YedjI hUQjMI hhGVMI ai gPI GdeSCdIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2008s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B335-358s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdbGfhf GdeUQis; (3GdbGfhf GdebGQfs; (3Mbhb GdeLfi Ydjgs; (3GdOYhi GdYehejI s; (3JMQjc GdOYhi s; (3GdGJgGe GdaQOj s; (3GdfjGHI GdYGeIs; (3eQMdI GdeMGceI s; (3GdOYhi GdLfGFjI s; (3LQGFe GdCehGd s; (3GdbVGA GdLfGFjs; (3GdEOYGA GdeOfj s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs